Influences of Fake News Type on Audiences’ Trust in News Source, News Forwarding and Commenting: A Case Study of Sina Weibo - luo, wenqian; Punnahitanond, Ratanasuda (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This paper investigates the impact of exposure to various types of fake news on Chinese audiences in terms of trust and behavioral reactions. According to Wardle and Derakhshan’s (2017) seven types of fake news – 1) satire/parody; 2) false connection; 3) misleading content; 4) false context; 5) imposter content; 6) manipulated content and 7) fabricated content, a survey study involving 300 Chinese Weibo users aged 18-35 years old with self-administered questionnaire was carried out through online and social media. The hypothesized effect of exposure to fake news type on trust, as well as on forwarding, and commenting behavior was tested by Multiple Regression and Linear Regression Analysis. Findings have shown that fabricated and manipulated content has a strong negative effect on trust whereas trust in news source is positively associated with news forwarding but not commenting behavior. Beyond its practical contributions, this study offers managerial implications for government offices, news media, and practitioners along with influencers to avert the spread of fake news, and also serves to inform the public about the significance of digital media literacy, which creates a barrier against the adverse effects of fake news.